Plan de negocios de la micro empresa Q´GENIAL para la comercialización de juegos didácticos dirigidos a los centros gerontológicos de la zona 5 y 8, año 2019. - Andrade Carranza, María Lorena (2019)
The Q'GENIAL Guayaquil micro-enterprise is dedicated to the elaboration of educational games that promote the distraction of people, to stimulate and develop motor skills and in turn exercise their mind. This is constituted from an endeavor of Eng. Luis Rodríguez Ojeda, which saw as an opportunity to produce these games in an artisan way after completing his career in the field of teaching for more than thirty years, supported by his ability of analysis, began its investigation of which would be the best options that can help the mental agility without turning a boring environment. As part of the relevance and identity that every business plan should seek, a study group was established for seniors who are in nursing homes or asylums in zones 5 and 8, with their intervention area addressing the few opportunities to perform individual and group activities, which will allow their distraction by staying active both physically and mentally. After arduous research it is determined that these games are very necessary in all stages of life, but in the third age they are especially recommended because they promote sociability, keep the mind active, help them to be positive and while they are agilitating the They are in a comfort of fun.